Respon Perempuan Milenial dalam Wacana Legalisasi Poligami di Aceh - Saka, Putri Ananda; Saka, Zidan Abdul Jabar (Institut Agama Islam Negeri Fattahul Muluk Papua, 2023)
The discourse on the legalization of polygamy in Aceh, which is contained in the Family Qanun, has become one of the issues that has generated pros and cons among the community. For the proponents and those who agree, legalizing polygamy is considered capable of minimizing the practice of nikah sirri and illegal polygamy. However, those who oppose it feel that this discourse is not an effective solution and instead creates new problems. This research focuses on the responses of Acehnese millennial women and their involvement in the discourse of legalizing polygamy in Aceh. Through a qualitative approach and literature study analyzed through gender politics theory and all conceptions, the research results were obtained: 1) 75% of informants strongly rejected the discourse on legalizing polygamy in Aceh because they considered that this plan would not be able to solve the problem of siri marriage or guarantee the rights of women and children as promised. Legalization of polygamy is considered to normalize polygamy and this further distorts the position of women in the family, 2) The involvement of women in bureaucracy and decision-making, especially millennials, is still very minimal, so in terms of their involvement in the discourse of legalizing polygamy in Aceh, it is still very lacking.